Advancing Law Enforcement Efficiency Through Predictive Policing Technologies - Rusmiyati Rusmiyati (Jurnal Puruhita, 2025)
Predictive policing has emerged as a transformative approach in modern law enforcement, utilizing statistical modeling, machine learning algorithms, and geospatial analytics to anticipate crime patterns and optimize resource deployment. This study investigates the effectiveness, challenges, and ethical implications of predictive policing systems implemented in urban environments. Using a mixed-methods design, the research analyzes crime data from three metropolitan jurisdictions, supported by interviews with 52 police officers, data analysts, and community stakeholders. Quantitative findings indicate that predictive models enhance hotspot identification accuracy by 33% and reduce targeted-area crime by 18% when combined with proactive patrol strategies. Predictive systems also improve resource allocation by minimizing redundant patrol routes and supporting evidence-based operational planning. However, interviews reveal concerns regarding algorithmic bias, data quality limitations, system opacity, and potential threats to civil liberties. The study concludes that predictive policing can significantly improve law enforcement performance when supported by transparent governance, robust data infrastructure, ethical safeguards, and continuous model evaluation. This research contributes to policing science by providing a comprehensive examination of predictive policing as a practical, technological, and ethical framework for modern public safety management.